Pengaruh Kreativitas Guru terhadap Prestasi Belajar Pendidikan Agama Islam siswa Kelas VII SMP Ma'arif NU 04 Darurrhmah Kecatamat Sukadana Kabupaten Lampung Timur - Asep Irawan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The study aims to describe how teacher creativity influences student learning interest in Islamic religious education subjects at SMP Ma'arif NU 04 Darurrohmah. The method used in this study is a descriptive quantitative method with a postpositivist approach (reality or facts). This research was conducted at SMP Ma'arif NU 04 Darurrohmah. This research is a population study because the respondents in the study amounted to 63 people which is the total number of students at the junior high school level. Data collection techniques were carried out by distributing questionnaires and documentation as well as data analysis using simple linear regression. The results of this study indicate that the creativity of teachers at SMP Ma'arif NU 04 Darurrohmah belongs to the poor category. This is evidenced by the mean = 54.62 and the interval of 54 – 58 the student interest in Islamic religious education is included in the low category with a mean = 53.89 and an interval is 47 – 53 and the effect of teacher creativity on student interest in learning Islamic religious education lessons at SMP Ma'arif NU 04 Darurrohmah show that there is an influence of teacher creativity on student learning interest based on the value of Fcount = 43.406 at the sig level of 0.000 and sig <α (0.000 <0.05) which, when the percentage is 41, 6% and the remaining 58.4% is influenced by other variables not discussed in this study.